Management of coking coal resources - Kumar, Dilip; Kumar, Deepak; ScienceDirect eBooks (Amsterdam : Elsevier Ltd., 2015)
Management of Coking Coal Resources provides a one-stop reference that focuses on sustainable mining practices using a four-point approach that includes the economical, governmental, societal, and environmental aspects of coal exploration, coking coal mining, and steelmaking applications. This type of approach galvanizes the excavation, processing methods, and end uses of coal as an energy and steelmaking source, thus ensuring that the supply of coking coal meets the future demands of the rapidly expanding economies in India and other developing countries. The book provides information on the strategic planning and revitalization of India's Jharia coalfield, addressing actionable plans for methods of extraction, master plans for mine fires, subsidence management, land use planning, and sustainable mining. Users will find a multidisciplinary reference that presents the broad range of applications, techniques, and methodologies used in maintaining coking coal quality from exploration through extraction. Provides a one-stop reference that focuses on sustainable mining practices using a four-point approach Includes the economical, governmental, societal, and environmental aspects of coal exploration, coking coal mining, and steelmaking applications Presents information on the strategic planning and revitalization of India's Jharia coalfield Includes a broad range of the applications, techniques, and methodologies used in maintaining coking coal quality from exploration through extraction.
Includes index.
Title details screen (ScienceDirect, viewed September 9, 2015).
Includes bibliographical references and index.
Elsevier
Keywords: Coking coal; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Coking coal; Electronic books